The League Composition Effect in Tournaments with Heterogeneous Players: An Empirical Analysis of Broiler Contracts - Levy, Armando; Vukina, Tomislav (Journal of Labor Economics, 2004)
We compare welfare effects of tournaments and piece rates in contracts with heterogeneous ability agents and demonstrate that tournaments that mix players of unequal abilities create a league composition effect. When leagues are fixed and the time horizon sufficiently long, piece rates improve welfare over tournaments. Using contract production data for broiler chickens, we estimate the variances of growers’ abilities, common production shock, and grower’s idiosyncratic shock. Growers' abilities are heterogeneous, and common production shocks are significant. Leagues in broiler tournaments disintegrate rapidly over time, suggesting that tournament contracts offer more welfare than piece rates.